Simeon the Righteous in rabbinic literature: a legend reinvented - Ṭroper, ʿAmram (Ancient Judaism and early Christianity, 2013)
The rabbinic traditions -- 2. Simeon the Righteous, the great assembly of Avot and the rabbinization of early Second Temple Judaism -- 3. Simeon the Righteous and the origins of the world's three pillars -- 4. Simeon the Righteous and the narcissistic Nazirite -- 5. Simeon the Righteous and Alexander the Great -- 6. Simeon the Righteous and the Temple of Onias -- 7. Simeon the Righteous in Second Temple chronology